Dateline Dehradun - Kanwar, Raj (Dehradun Writer's Combine, 2020)
What was Dehra Dun like in the 1930s? What was then its administrative structure? Who was its first District Magistrate? And who was its first Superintendent of Police? Who are its prominent citizens? And who are its well known authors? What is the origin and growth of its famous schools that has given Dehra Dun the sobriquet of THE SCHOOL TOWN OF INDIA? What are its world-famous Institutions and how and when those were established? How and when Dehra Dun became the headquarters of the Oil & Natural Gas Commission and in what way that changed the town$1 (Bs face? Why did Jawaharlal Nehru love Dehra Dun, and why did Indira Gandhi frequently visit the town? And what were those early struggling days of well known author Ruskin Bond, and why did he visit the main Post Office so frequently? I believe that not many of my fellow residents know what Dehra Dun was like in those early years and how it grew from a small town into a flourishing city. DATELINE DEHRA DUN answers those questions.s
Keywords: Dehradun-Institutions and personalities -- Dehradun-History and culture; Dehradun-Schools